Does the Islamic Accounting Profit Methodology Create Maslahah?: Comparison between Conventional Bank and Islamic Bank in Practice - Supriyanto, Trisiladi (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study aims to find the Islamic Accounting Profit System and its application in financial products in Islamic banks is in accordance with the objectives of the Islamic Purpose (maqashid sharia) to achieve economic justice in which equitable distribution of income and wealth is created. The problem is that in Indonesia, the Cleric has created Fatwa or Islamic Law no. 84/MUI/2012 that allows banks to use profit methodology’s either in the form of an annuity system (Thariqah al-Tanaqushiyyah) using the time value of money calculation or through a proportional system (Thariqah Mubasyirah) using an economic value system whereby profit is evenly distributed up to maturity.   This research is conducted via a literature review, field studies and inferential research, and it enhances the research and the application of the profit rate as it was previously applied in Islamic financial institutions in Indonesia (3 Banks: Bank Muammalat, Bank Danamon Syariah and Bank Permata Syariah) and Bank in Bangladesh and Malaysia. The results from the research is that the distribution of investment income in Islamic banks that uses the concept of profit rate (the economic principle for the value of time) with an even distribution between principal and margins on short-term transactions (proportional method), giving a better welfare to banks and customers. Conclusion Sharia Bank in the future should use Proportional Methodology in applying accounting that in accordance with sharia principle.